Business model design: Novelty and efficiency - Quirino, R.; Dias, Á. (Competitive drivers for improving future business performance, 2021)
Business model design refers to the design of transactions operated by an organization represented by the content, structure, and governance of all transactions that occur in an organization in order to create value through exploration of a business opportunity. This study has as objective to analyze the impact of one or more business model design has on the performance. Through the conduct of surveys, a sample of 30 companies was collected between Europe and Brazil. The results showed that it was not possible to obtain correlations to validate the hypotheses, due to the great difficulty of obtaining the data by the companies, thus leading to a reduced number of respondents. This study contributes significantly to the theory of innovation and entrepreneurship, as a response to a latent need on the part of the literature to consistently homogenize the understanding about the theme and clear recommendations and practices for management.